G-Quadruplex-Binding Proteins: Promising Targets for Drug Design - Huiling Shu; Rongxin Zhang; Ke Xiao; Jing Yang; Xiao Sun (Biomolecules, 2022)
G-quadruplexes (G4s) are non-canonical secondary nucleic acid structures. Sequences with the potential to form G4s are abundant in regulatory regions of the genome including telomeres, promoters and 5′ non-coding regions, indicating they fulfill important genome regulatory functions. Generally, G4s perform various biological functions by interacting with proteins. In recent years, an increasing number of G-quadruplex-binding proteins have been identified with biochemical experiments. G4-binding proteins are involved in vital cellular processes such as telomere maintenance, DNA replication, gene transcription, mRNA processing. Therefore, G4-binding proteins are also associated with various human diseases. An intensive study of G4-protein interactions provides an attractive approach for potential therapeutics and these proteins can be considered as drug targets for novel medical treatment. In this review, we present biological functions and structural properties of G4-binding proteins, and discuss how to exploit G4-protein interactions to develop new therapeutic targets.